Safety of conversion facilities and uranium enrichment facilities : specific safety guide (International Atomic Energy Agency, 2010)
This safety guide supplements the safety requirements publication, Safety of fuel cycle facilities, and addresses all the stages in the life cycle of conversion facilities (CFs) and enrichment facilities (EFs), with emphasis placed on design and operation. It describes the actions, conditions and procedures for meeting safety requirements and deals specifically with the handling, processing and storage of depleted, natural and low enriched uranium. The publication is intended to be of use to designers, operating organizations and regulators for ensuring the safety of conversion and enrichment facilities.--Publisher's description.
"May 2010."
Keywords: Nuclear facilities -- Safety measures.; Uranium enrichment -- Safety measures.; elektronické knihy; electronic books